Potential of Kersen Leaf Extract (Muntingia calabura L) and Basil Leaf Extract (Ocimum basilicum L.) as Natural Antibacterial Candidates against Salmonella typhi - Mustika Weni; Sri Marfuati; Hikmah Fitriani (Universitas Djuanda, 2025)
Salmonella typhi remains a global health issue with rising antibiotic resistance, necessitating alternative natural therapies. Kersen (Muntingia calabura L.) and basil (Ocimum basilicum L.) leaves contain bioactive compounds with antibacterial potential. The purpose of this research was to examine the antibacterial activity of kersen and basil leaf ethanol extracts against Salmonella typhi at various concentrations. The research applied an experimental Post-Test Only Control Group Design. Antibacterial activity assessment was performed using the well diffusion method with varying extract concentrations of 20%, 35%, 45%, 50%, and 75%. Data analysis was performed using the Shapiro–Wilk test was used to examine data normality, while group differences were evaluated with the Kruskal–Wallis non-parametric test. Kersen extract contained saponins, tannins, alkaloids, flavonoids; basil extract contained phenolics, saponins, tannins, alkaloids, steroids, flavonoids. Both showed concentration-dependent inhibition. At 75%, inhibition zones reached 13.15 mm (strong), while the lowest were 4.70 mm (kersen, weak) and 7.30 mm (basil, moderate). Negative control showed no activity. Statistical test p=0.005 confirmed significant differences between groups. Ethanol extracts of kersen and basil leaves possess significant antibacterial activity against S. typhi, supporting their potential as natural phytotherapeutics for typhoid.